Impact of protein source from legume forages on lipid regulation and growth on native ram lambs reared extensively in the south coast of West Java, Indonesia - UJANG HIDAYAT TANUWIRIA; ANDI MUSHAWWIR; MARDIATI ZAIN; DESPAL DESPAL (Society for Indonesian Biodiversity, 2023)
Abstract. Tanuwiria UH, Mushawwir A, Zain M, Despal D. 2023. Impact of protein source from legume forages on lipid regulation and growth on native ram lambs reared extensively in the south coast of West Java, Indonesia. Biodiversitas 24: 4183-4192. This investigation was carried out in three different locations to examine the impact of legume forage as a protein source on lipid regulation and growth. This study used 120 rams, consisting of 40 rams in each location (Garut, Cianjur, Sukabumi) spread along the South Coast of West Java. Physical environmental conditions were recorded during the study. Ram lambs at each location were divided into four groups; one group only received a basal diet (Setaria/Setaria sphacelata), and the other three groups were each given additional legumes (calliandra/Calliandra calothyrsus, lamtoro/Leucaena leucocephala, and moringa/Moringa oleifera). Blood samples were collected every two weeks during the 16 weeks experiment. The blood sampling was handled based on standard procedures to prevent sample damage, and the body weight was measured every two weeks. Sample analysis related to lipid regulation and creatine kinase activity was measured using spectrophotometric techniques according to the instructions of the Kit Randox protocol and analysis of blood plasma fatty acids were analyzed by gas chromatography. The research results show that legumes as a protein source can regulate through molecular signaling to decrease lipid levels, saturated fatty acids, and lipid transport in the extracellular fluid, but increase unsaturated fatty acid and the growth rate of ram lambs. Based on the results of the current study, it can be a strong basis for the development of nutrigenomic aspects of protein for small ruminants, accompanied by studies of the ages of different ruminant samples.